Intra-cavity patterning - new method of single mode emission enhancement - Czyszanowski, Tomasz; Volet, Nicolas; Walczak, Jarosław; Dems, Maciej; Sarzała, Robert (Photonics Letters of Poland, 2014)
We demonstrate the results of numerical simulations of 1.3μm InAlGaAs/InP VCSEL with ring pattern etched at the interface between the cavity and top DBR. We show that proposed design offers selective confinement of the fundamental mode and strong discrimination of higher order modes. Consequently VCSEL with ring confinement is capable to operate in broad range of injected currents in the single mode regime which facilitates improvement of the maximal emitted power and increase of the wavelength tuning range with very narrow spectral characteristics. Full Text: PDF References C. Jung, R. Jäger, M. Grabherr, P. Schnitzer, R. Michalzik, B. Weigl, S. Müller, K.J. Ebeling, "4.8 mW singlemode oxide confined top-surface emitting vertical-cavity laser diodes", Electron. Lett. 33, 1790 (1997). CrossRef A.-S. Gadallah, R. Michalzik, "High-Output-Power Single-Higher-Order Transverse Mode VCSEL With Shallow Surface Relief", IEEE Photon. Technol. Lett. 23, 1040 (2011). CrossRef D. Zhou, L.J. Mawst, "High-power single-mode antiresonant reflecting optical waveguide-type vertical-cavity surface-emitting lasers", IEEE J. Quantum Elect. 38, 1599 (2002). CrossRef E. Kapon, A. Sirbu, "Long-wavelength VCSELs: Power-efficient answer", Nat. Phot. 3, 27 (2009). CrossRef A.J. Danner, J.J. Raftery, T. Kim, P.O. Leisher, A.V. Giannopoulos, K.D. Choquette, "Progress in Photonic Crystal Vertical Cavity Lasers", IEICE Trans. Electron. E88–C, 944 (2005). DirectLink N. Volet, T. Czyszanowski, J. Walczak, L. Mutter, B. Dwir, Z. Micković, P. Gallo, V. Iakovlev, A. Sirbu, A. Caliman, A. Mereuta, E. Kapon, "Improved single-mode emission characteristics of long-wavelength wafer-fused vertical-cavity surface-emitting lasers by intra-cavity patterning", Proc. SPIE 8639, 86390S (2013). CrossRef A. Sirbu, V. Iakovelv, A. Mereuta, A. Caliman, G. Suruceanu, E. Kapon, "Wafer-fused heterostructures: application to vertical cavity surface-emitting lasers emitting in the 1310 nm band", Semicond. Sci. Technol. 26, 014016 (2011). CrossRef M. Dems, R. Kotynski, K. Panajotov, "PlaneWave Admittance Method — a novel approach for determining the electromagnetic modes in photonic structures", Opt. Exp. 13, 3196 (2005). CrossRef R.P. Sarzala, W. Nakwaski, "Optimization of 1.3 µm GaAs-based oxide-confined (GaIn)(NAs) vertical-cavity surface-emitting lasers for low-threshold room-temperature operation", J. Phys., Condens. Matter 16, S3121 (2004). CrossRef D. Xu, C. Tong, S.F. Yoon, W. Fan, D.H. Zhang, M. Wasiak, Ł. Piskorski, K. Gutowski, R.P. Sarzała, W. Nakwaski, "Room-temperature continuous-wave operation of the In(Ga)As/GaAs quantum-dot VCSELs for the 1.3 µm optical-fibre communication", Semicond. Sci. Technol. 24, 055003 (2009). CrossRef T. Czyszanowski, M. Dems, R.P. Sarzała, K. Panajotov, K.D. Choquette, "Photonic Crystal VCSELs: Detailed Comparison of Experimental and Theoretical Spectral Characteristics", IEEE J. Select. Top. Quant. Electron. 19, 1701908 (2013). CrossRef W. Nakwaski, "Thermal conductivity of binary, ternary, and quaternary III-V compounds", J. Appl. Phys. 64, 159 (1989). CrossRef J. Piprek, J. K.White, A.J. SpringThorpe, "What limits the maximum output power of long-wavelength AlGaInAs/InP laser diodes?", IEEE J. Quantum Electron. 38, 1253 (2002). CrossRef S. Adachi, "GaAs, AlAs, and Al x Ga1−x As: Material parameters for use in research and device applications", J. Appl. Phys. 58, R1 (1985). CrossRef S. Gehrsitz, F.K. Reinhart, C. Gourgon, N. Herres, A. Vonlanthen, H. Sigga, "The refractive index of AlxGa1−xAs below the band gap: Accurate determination and empirical modeling", J. Appl. Phys. 87, 7825 (2000). CrossRef S. Adachi, "Physical Properties of III-V Semiconductor Compounds: InP, InAs, GaAs, GaP, InGaAs, and InGaAsP", Physical Properties of III-V Semiconductor Compounds (New York, NY, USA, Wiley 1992). CrossRef R.J. Sladek, "Thermal Conductivity of Indium-Thallium Alloys at Low Temperatures", Phys. Rev. 97, 902 (1955). CrossRef N.V. Zavaritskii, A.G. Zeldovich, "Thermal Conductivity Of Technical Materials At Low Temperatures", Zh. Tekh. Fiz. 26, 2032 (1956). L. Mutter, V. Iakovlev, A. Caliman, A. Mereuta, A. Sirbu, E. Kapon, "1.3 μm-wavelength phase-locked VCSEL arrays incorporating patterned tunnel junction", Opt. Exp. 17, 8558 (2009). CrossRef L. Mutter, B. Dwir, A. Caliman, V. Iakovlev, A. Mereuta, A. Sirbu, E. Kapon, "Intra-cavity patterning for mode control in 1.3μm coupled VCSEL arrays", Opt. Exp. 19, 4827 (2011). CrossRef E. Kapon, A. Sirbu, "Long-wavelength VCSELs: Power-efficient answer", Nat. Phot. 3, 27 (2009). CrossRef T. Czyszanowski, M. Dems, R.P. Sarzała, W. Nakwaski, K. Panajotov, "Precise Lateral Mode Control in Photonic Crystal Vertical-Cavity Surface-Emitting Lasers", IEEE J. Quantum Electron 47, 1291 (2011). CrossRef